Arbuscular Mycorrhizal Fungus Alters Root System Architecture in Camellia sinensis L. as Revealed by RNA-Seq Analysis - Chen, Weili; Ye, Tao; Sun, Qinyu; Niu, Tingting; Zhang, Jiaxia (Frontiers in Plant Science, 2021)
Arbuscular mycorrhizal fungus (AMF), forming symbiosis with most terrestrial plants, strongly modulate root system architecture (RSA), which is the main characteristic of root in soil, to improve plant growth and development. So far, the studies of AMF on tea plant seedlings are few and the relevant molecular mechanism is not deciphered. In this study, the six-month-old cutting seedlings of tea plant cultivar ‘Wancha No.4’ were inoculated with an AMF isolate, Rhizophagus intraradices BGC JX04B and harvested after 6 months of growth. The indexes of RSA and sugar contents in root were determined. The transcriptome data in root tips of mycorrhizal and non-mycorrhizal cutting-seedlings were obtained by RNA-Seq analysis. The results showed that AMF significantly decreased plant growth, but increased the sucrose content in root and the higher classes of lateral root formation (3rd and 4th lateral root). We identified 2047 differentially expressed genes (DEGs) based on the transcriptome data, and DEGs involved in metabolisms of phosphorus (42 DEGs), sugar (39), lipid (67) and plant hormones (39) were excavated out. Variation partitioning analysis showed all these four categories modulated the RSA. In phosphorus (P) metabolism, phosphate transport and release (DEGs related to purple acid phosphatase) were promoted by AMF inoculation, while DEGs of sugar transport protein in sugar metabolism were down-regulated. Lipid metabolism might not be responsible for root branching but for AMF propagation. As respect to phytohormones, DEGs of auxin (13), ethylene (14) and abscisic acid (5) were extensively affected by AMF inoculation, especially for auxin and ethylene. The further partial least squares structural equation modeling analysis indicated that pathways of P metabolism and auxin, as well as the direct way of AMF inoculation, were of the most importance in AMF promoting root branching, while ethylene performed a negative role. Overall, our data revealed the alterations of genome-wide gene expression in tea plant root after inoculated with AMF and provided a molecular basis for the regulatory mechanism of RSA (mainly root branching) changes induced by AMF.